SUKU MALAYU: SISTEM MATRILINEAL DAN BUDAYA PERUNGGU DI MINANGKABAU - Andar Indra Sastra (Melayu Arts and Performance Journal, 2018)
ABSTRACT The goal of this article is to investigate the existence of the Malay ethnic group in connection with the matrilineal system and the bronze culture in Minangkabau. The Malay (Minang) ethnic group is one of the ethnic groups (or clans) with the largest population of all the different ethnic groups in Minangkabau. The matrilineal system is one of the strongest identities – or icons – for recognizing the unique community of Minangkabau. This unique characteristic continues to exist in spite of the fact that the majority of the Minangkabau people are strict Muslims. The matrilineal system refers genealogically to the female line of descent and is centered in the traditional gadang house which is the identity of the ethnic group in the culture of the Malay Minangkabau community. The gadang house is a symbol of status and ethnicity in the social system of the Minangkabau community – the group known as urang asa (original pioneers). One of the identities that strengthens the existence of the urang asa group in the past is marked by the presence of bronze music in the form of salabuhan (a set of) talempong and aguang (gong) – a type of bronze music. The problems discussed in this article are: (1) the Malay ethnic group in Minangkabau; (2) the matrilineal system and bronze culture in Minangkabau. A qualitative method is the basic foundation for this research. The research results show that the Malay ethnic group in Minangkabau first appeared as a result of the dissemination of the inhabitants of the Malay Dharmasraya kingdom and this was subsequently continued by Adityawarman through the Pagaruyuang kingdom. The Malay ethnic group not only follows a matrilineal system but also supports the bronze culture. Keywords: malay ethnic group, matrilineal system, bronze culture, Minangkabau  ABSTRAK Tujuan artikel ini mengungkap bagaimana keberadaan suku Malayu dalam kaitannya dengan sistem matrilenal, dan budaya perunggu di Minangkabau. Suku Malayu (Minang) adalah salah suku (klan) yang tergolong banyak populasinya dalam kelompok suku Minangkabau. Sistem matrilineal adalah salah satu identitas – icon – terkuat untuk mengenali masyarakat Minangkabau – unik. Keunikan tersebut tetap bertahan walapun masyarakat Minangkabau penganut Islam yang taat. Sistem matrilineal secara geneologis merujk pada garis keturuan ibu dan berpusat pada rumah gadang (sebutan rumah adat) sebagai identitas kelompok suku dalam kebudayaan masyarakat Malayu Minangkabau. Rumah gadang menjadi simbol status dan kesukuan dalam sistem sosial masyarakat Minangkabau – kelompok urang asa (peneruka asal). Salah satu identitas yang menguatkan terhadap keberadaan kelompok urang asa pada masa lalu ditandai atau memiliki alat jenis musik perunggu salabuhan (seperangkat) talempong dan  aguang (gong) – jenis musik perunggu. Masalah yang dibaicakan dalam artikel ini: (1) suku malayu di Minangkabau; (2) sistem matrilineal dan budaya perunggu di Minangkabau. Metode kualitatif menjadi dasar dilakukannya penelitain ini. Hasil penelitian ini; suku Malayu di Minangkabau bermula dari penyebaran penduduk kerajaan Melayu Dharmasraya dan kemudian dilanjutkan Adytiawarman melalui kerjaan Pagaruyuang. Suku Malayu, di samping menganut sistem matrilineal, juga sebagai pendukung kebudayaan perunggu.